2014
DOI: 10.3141/2466-13
|View full text |Cite
|
Sign up to set email alerts
|

Travel Time Distribution under Interrupted Flow and Application to Travel Time Reliability

Abstract: The travel time distribution under interrupted flow based on radio frequency identification–detected data is analyzed. The urban road network studied is in downtown Nanjing, Jiangsu Province, in China, where video cameras and radio frequency equipment are installed at some arterial links to acquire traffic flow data including vehicle type, passing time, and spot speed. On the basis of the radio frequency identification data, the travel time distribution under interrupted flow shows a bimodal curve instead of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Considering a free-flow traffic condition, the travel times of vehicles traversing a signalized link directly depend on the signal controls and their distribution appears to be bimodal [1][2][3][4][5]7], which features two clusters of travel times corresponding to the states of nonstopped and stopped vehicles, respectively. To achieve the state partitions, a two-component mixed normal distribution, rather than the skewed mixture models (e.g., the components are both lognormal distributions), is adopted to obtain the travel times in state 1 and state 2 individually as a tradeoff between computation complexity and explanatory power [18].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering a free-flow traffic condition, the travel times of vehicles traversing a signalized link directly depend on the signal controls and their distribution appears to be bimodal [1][2][3][4][5]7], which features two clusters of travel times corresponding to the states of nonstopped and stopped vehicles, respectively. To achieve the state partitions, a two-component mixed normal distribution, rather than the skewed mixture models (e.g., the components are both lognormal distributions), is adopted to obtain the travel times in state 1 and state 2 individually as a tradeoff between computation complexity and explanatory power [18].…”
Section: Methodsmentioning
confidence: 99%
“…Signal delay is the primary factor that influences travel time patterns on an urban link [3]. Unfortunately, in most cases, the signal control plans at intersections are generally unknown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Susilawati et al (9) found that bimodal travel times were more likely to occur on shorter links with coordinated signal control, but did not investigate the impact of the traffic control scheme on the distribution. Other research has focused on model development (10), and the relationship between bimodal travel time distributions and travel time reliability (11,12) and congestion identification (13).…”
Section: Literature Reviewmentioning
confidence: 99%